Arsenic-Related Health Risk Assessment of Realgar-Containing NiuHuangJieDu Tablets in Healthy Volunteers Po Administration - Wu, Xiao; Yan, Ruoning; Guan, Rong; Du, Yi; Liu, Yuexin; Wu, Shanhu; Zhu, Song; Song, Min; Hang, Taijun (Frontiers in Pharmacology, 2022)
Realgar, an arsenic-containing traditional Chinese medicine (TCM) of As2S2, has significant therapeutic effects for hundreds of years. NiuHuangJieDu Tablets (NHJDT) is one of the most commonly prescribed realgar-containing preparations for the treatment of sore throat, swelling and aching of gum. However, realgar-containing TCMs raise great safety concerns due to the adverse effects reported by arsenic poisoning. In this study, the arsenic related health risk assessment of NHJDT was conducted in healthy volunteers after single and multiple doses oral administration. Blood, plasma and urine samples were collected after dosing at predetermined time points or periods. Simple, rapid, and sensitive methods were established for the quantification of total arsenic and arsenic speciation in biological samples. The total arsenic and arsenic speciation were determined by hydride generation-atomic fluorescence spectrometry (HG-AFS) and high performance liquid chromatography-hydride generation-atomic fluorescence spectrometry (HPLC-HG-AFS), respectively. No significant fluctuation of total arsenic was observed in human blood, and no traces of arsenic speciation were found in human plasma. Dimethylarsenic acid (DMA) was detected as the predominated arsenic species in human urine after dosing. Therapeutic dose administration of NHJDT was relatively safe in single dose for the limited blood arsenic exposure, but long-term medication may still pose health risks due to the accumulation of arsenics in blood and its extremely slow excretion rate. Therefore, arsenic exposure should be carefully monitored during realgar-containing TCMs medication especially for long-term regimen. The results obtained in this study will provide scientific references for the clinical application of realgar and its-containing TCMs.